Is the Paris Agreement the Breakthrough to an International Climate Agreement? - Renate Neubäumer (Wirtschaftsdienst)
Abstract The article analyses how the CO2 emissions of the world’s ten largest polluters have evolved in the past and will evolve by 2030 if the member countries of the Paris Agreement comply with the NDCs. By 2030, the CO2-budgets for reaching the 1.5- or 2-degree target will be exhausted to a significant extent. Industrialized countries cannot stop climate change by reducing their own emissions alone. Therefore, they should change their strategy and cooperate more closely with developing and emerging countries and support them in reducing their CO2 emissions. Additionally, they should take more measures to adapt to climate change.